Effect of static magnetic field on bone mineral content in aging rats - Cejic, Dimitrije; De Luka, Silvio (Medicinski podmladak, 2022)
ABSTRACT Introduction: Aging is defined as a consequence of progressive accumulation of metabolic waste, which results in development of various disorders in the structure and function of cells over a number of years. Aging is followed by loss of bone tissue, and bones become less firm. The cycle of bone remodeling with age becomes longer, and the degree of bone mineralization decreases. Static magnetic fields (SMF) are stable magnetic fields that can be natural or artificial. SMF of moderate intensity (1mT-1T) affects physiological processes, cells, genetic material, behavior and development. So far, numerous studies have shown different effects of static magnetic fields on cell cultures, experimental animals, and the human population. Aim: Aim of this study was to determine the effect of static magnetic field (SMF) on bone mineral content (BMC) values in aging rats. Material and methods: Wistar rats, 3 years old, were used in the experiment. A total of 18 animals were divided into two groups: exposed (experimental group) and unexposed (control group). 9 experimental group rats were exposed to 30mT intensity static magnetic field for 10 weeks, while 9 control group rats were not exposed to the effect of the static magnetic field. BMC was measured by DXA (Dual-Energy X-Ray Absorptiometry). Results: Based on the experiment, it was found that after exposure to the static magnetic field, in the experimental group there is a statistically significant increase in the value of BMC in the trunk region and ribs region. In all other regions of interest: head, legs, pelvic bone, spine, total BMC- there were no statistically significant changes in BMC values. Conclusion: In the conducted experiment, a higher increase in the value of BMC was found in animals exposed to the SMF, compared to animals that were not exposed to the static magnetic field. Keywords: aging, static magnetic field, bone mineral content